2014
DOI: 10.1103/physrevd.89.064037
|View full text |Cite
|
Sign up to set email alerts
|

Mismodeling in gravitational-wave astronomy: The trouble with templates

Abstract: Waveform templates are a powerful tool for extracting and characterizing gravitational wave signals, acting as highly restrictive priors on the signal morphologies that allow us to extract weak events buried deep in the instrumental noise. The templates map the waveform shapes to physical parameters, thus allowing us to produce posterior probability distributions for these parameters. However, there are attendant dangers in using highly restrictive signal priors. If strong field gravity is not accurately descr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 90 publications
1
68
0
Order By: Relevance
“…An explicit demonstration is left for future work. On the other hand, if the signal waveform is not among any of the template models, then fundamental bias can make it difficult to reliably pinpoint the underlying nature of the violation [26,[59][60][61][62]. This remains an open problem for ringdown as well.…”
Section: Discussionmentioning
confidence: 99%
“…An explicit demonstration is left for future work. On the other hand, if the signal waveform is not among any of the template models, then fundamental bias can make it difficult to reliably pinpoint the underlying nature of the violation [26,[59][60][61][62]. This remains an open problem for ringdown as well.…”
Section: Discussionmentioning
confidence: 99%
“…Note that depending on the EOS those differences can be smaller than or comparable to what we have found in dynamical scalarization (see Table II). At SNR around 30-35, deviations from general relativity might also be observable even in cases in which the onset of dynamical scalarization happens at orbital frequencies above 50 Hz [28,61]. It will be interesting to investigate in the future the detectability of tidal effects in the presence of dynamical scalarization.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies carried out in Refs. [28,61], which use scalar-tensor templates in the frequency domain, rely on the scalar-charge evolution and numerical-relativity simulations of Refs. [9,11], which concluded that advanced detectors operating at a signal-to-noise ratio (SNR) of 10 will be able to constrain dynamical scalarization only if the system scalarizes at low enough orbital frequencies, e.g., ≤ 50 Hz, so that a sufficient number of GW cycles emitted during the dynamical-scalarization phase can contribute to the accumulated SNR.…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown explicitly in [63], at least in FJBD theory, these higherorder PN corrections only affect a Fisher analysis like ours by at most 10%. The addition of many terms in the GW phase at multiple PN orders is not only unnecessary, but actually counterproductive as it dilutes the ability to extract information from the signal (as pointed out in [75,76] and verified in [73]). …”
mentioning
confidence: 99%